The Influence of Effectiveness and Quality of Information Systems Based on Enterprise Resource Planning (ERP) on Employee Performance of PT Swabina Gatra - Wulandari, Fischa Aditiyah; Suwarno, Suwarno (Universitas Muhammadiyah Gresik, 2024)
PT. Swabina Gatra is a national private company that has played an important role in the industrial sector, especially in the provision of goods and services in Indonesia. This study aims to examine the impact of the effectiveness and quality of Enterprise Resource Planning (ERP)-based information systems on employee productivity and adaptation while strengthening the literature on the relationship between Enterprise Resource Planning (ERP) and employee performance. This study is quantitative. The sample of this study consisted of 40 respondents who were employees of PT. Swabina Gatra who worked with the Enterprise Resource Planning (ERP) system. This study used instrument tests such as validity and reliability tests, normality tests, multicollinearity tests, and autocorrelation tests, followed by hypothesis tests and determination tests. The results of the study revealed that the effectiveness variable did not have a significant influence on employee performance, while the quality variable showed a significant influence on employee performance.